Malnutrition and infection in a typical rural Guatemalan Village: Lessons for the planning of preventive measures - Mata Jiménez, Leonardo (2010)
A long-term prospective study of fetal and postnatal growth and possible influenceson growth was initiated in 1963in a Guatemalan village.A high proportion of the infants were of low birth weight and they were more at risk to death in the first year of life than infants with higher birth weights.The latter also had a better chance of survivingthe criticalweaning period. There was a very high prevalenceof infection in infancy and childhood, and a high proportion of infants with elevated cord IgM levels suggests that there had been intrauterine antigenic stimulation. Postnatal growth was generallysatisfactory for the first 8-16 weeksof life but by one year the majority of the children were belowthe standard for height and weight,and growth continued to be unsatisfactory until the third or fourth year. There was evidencethat growth was being retarded by infections and that they had their greatest effect during the second year of life. It is suggested that maternal infections are an important component of the etiology of fetal growth retardation and that planning of priorities for maternal and child health in developing countries should take this into account